Aspidistra erythrocephala sp. nov. (Asparagaceae) from Guangxi, China - Liang, Yong-Yan; Liu, Jing; Huang, Yu-Song; Lin, Chun-Rui (Phytotaxa, 2016)
Aspidistra Ker-Gawler (1822: 628) is native to eastern and southeastern Asia, particularly China and Vietnam. Only a few species are known from Thailand, Laos, Malaysia, Japan, and India. Since in 1822, when A. lurida Ker-Gawler (1822: 628) was described from a cultivated plant, the species number increased very slowly to 11 in 1980. Since then, the species number began to grow rapidly, especially in China and Vietnam, currently increasing the total number of species to over 150. In recent years, after field surveys in southwest Guangxi (southern China), several new species of Aspidistra have been discovered and described (Lin & Liu 2011, Lin et al. 2012, 2013, 2015, Meng et al. 2014, Huang et al. 2015).